1998
DOI: 10.1074/jbc.273.16.9501
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Activation by REG Molecules Lacking Homolog-specific Inserts

Abstract: The peptidase activities of eukaryotic proteasomes are markedly activated by the 11 S REG or PA28. The three identified REG subunits, designated ␣, ␤, and ␥, differ significantly in sequence over a short span of 15-30 amino acids that we call homolog-specific inserts. These inserts were deleted from each REG to produce the mutant proteins REG␣⌬i, REG␤⌬i, and REG␥⌬i. The purified recombinant proteins were then tested for their ability to oligomerize and activate the proteasome. Both REG␣⌬i and REG␥⌬i formed app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…Important secondary structural features, such as proline residues in predicted turns, are highly conserved among the three classes of REG proteins. However, a nonessential flexible loop region termed the homolog-specific insert region present N-terminal to the activation domain shows little sequence conservation between the REG classes (38). This region does show conservation within the classes and the alignment of the vertebrate and invertebrate REG sequences revealed a conserved domain that resembled a c-Myc nuclear localization domain present in the human oncogene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Important secondary structural features, such as proline residues in predicted turns, are highly conserved among the three classes of REG proteins. However, a nonessential flexible loop region termed the homolog-specific insert region present N-terminal to the activation domain shows little sequence conservation between the REG classes (38). This region does show conservation within the classes and the alignment of the vertebrate and invertebrate REG sequences revealed a conserved domain that resembled a c-Myc nuclear localization domain present in the human oncogene.…”
Section: Resultsmentioning
confidence: 99%
“…REG␣ and REG␤ molecules that lack the homolog-specific insert regions are functional in binding and activating the 20 S proteasome (38). It has been proposed for REG␣ and REG␤ that the homolog-specific insert regions could function in targeting the proteasome activator to chaperonins or the calnexin⅐TAP complex (38).…”
Section: Dreg␥ a Drosophila Proteasome Regulatormentioning
confidence: 99%
“…This method was also used to obtain the REG␤ mutants described in these studies. A detailed description on how to make a REG␤ mutant and REG␣241␥8 using this method can be found in an article by Zhang et al (38).…”
Section: Methodsmentioning
confidence: 99%
“…There are two reports that REG␤ is inactive (36,37), and it has recently been proposed that REG␤ functions only to modulate the activity of REG␣ (37). However, several publications from our laboratory have shown that REG␤, by itself, activates the proteasome (34,35,38). Moreover, a single-site mutation in the presumed activation region of REG␤ produces an inactive protein, REG␤(N135Y), that is still capable of binding the proteasome (35).…”
mentioning
confidence: 99%
“…There are three isoforms of PA28: PA28␣, PA28␤, and PA28␥, sharing about 50% amino acid sequence identity (20). The ␣ and ␤ isoforms form a complex with 20 S proteasome in the form of a heptamer ring of three PA28␣ and four PA28␤ or three PA28␤ and four PA28␣ (21,22). The crystal structure of recombinant human PA28␣ has been recently resolved in the form of a self-assembled heptamer ring (23).…”
mentioning
confidence: 99%